MANAJEMEN PENDIDIKAN DALAM KONSTELASI PROGRESIVISME (Telaah Filsafat Pendidikan John Dewey) - Supriatna, Ucup (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2021)
This study aims to generalize the education management system in the constellation of John Dewey's philosophy of progressivism. As a qualitative-descriptive research, this research was conducted using library research. Research data obtained through primary and secondary literature on the philosophy of progressivism John Dewey. The data collection technique is done by documentation. Researchers document the educational thinking of John Dewey's progressivism, then describe it methodologically. Data analysis was carried out by data reduction, data presentation, and data analysis. The researcher reduces John Dewey's educational thought of progressivism, presents it systematically, then analyzes this thought in the education management system. The results showed; First, humans as educational human resources must be given roles and tasks according to their talents and interests. Humans are agents of change in education. Second, education has a forward and progressive orientation. This is a form of criticism of the scholastic education management system. Progressive education can be realized through a progressive curriculum reconstruction. Third, school educational institutions are miniatures of life in society. Therefore, schools need to be in symbiosis with the community in order to realize educational goals. Fourth, humans who learn have academic freedom. In the sense that humans can learn whatever they want to develop their potential and skills. These four things are the spark of progressive educational thinking according to John Dewey. Then these four things can be realized through progressive education management.